G426(P) Neurodevelopmental follow-up of extremely preterm babies – comparing current practice with nice guidelines. (May 2019) - Storey, C
Abstract : Background and objectives: The August 2017 NICE Guidelines on developmental follow-up of children and young people has introduced a new recommendation that babies born before 28 weeks gestational age have formal educational psychology follow-up at four years of age. This is a change from previous guidelines, which recommended discharging preterm babies after a normal neurodevelopmental assessment at two years corrected gestational age. The purpose of the study was to assess whether the four-year educational psychology follow-up would provide any added value, and what level of resources would be required to implement the guidelines in this level-2 neonatal unit. Methods: This retrospective study looked at all babies born under 28 weeks in 2012 in a particular unit, to see their neonatal, two year and four year outcomes. Data was gathered from neonatal records and medical notes, as well as phone calls to the parents of those children who had been discharged, to get qualitative feedback about behaviour and school performance. Results: Of the 17 extremely preterm babies born in this level 2 unit in 2012, approximately two thirds of babies survived. Of the surviving babies, half (7) were developmentally normal at their two year follow-up, and were discharged. The other half were under neurodevelopmental follow-up for mild developmental delay, ASD or language delay. Of those children who were developmentally normal at two years, all but one were in mainstream education and none had been referred to community paediatric services. The child who was not in mainstream education was being home-schooled for unrelated reasons. Discussion: The introduction of four-year follow-up by an educational psychologist would necessitate significant changes to current service provision. Since the children who were discharged at two years have not gone on to require paediatric services, it is uncertain whether the significant cost incurred by having four year follow-up, and thus being compliant with the 2017 NICE Guidelines, would be justifiable. Further studies around longer term neurodevelopmental and psychological outcomes may be informative.